Global Marketing Strategy of Indomie in Facing Competition in the Nigerian Market - Muhammad Rifqi Salichin; Moza Muhammad Althaf; Mochamad Zidane Farrel Dermawan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study analyzes the global marketing strategy of Indomie, a flagship instant noodle product of PT Indofood Sukses Makmur, in penetrating and sustaining its competitive position in the Nigerian market. Nigeria represents one of the most strategically significant international markets for Indomie, where the brand has achieved a level of cultural embedding so deep that Nigerian consumers frequently use "Indomie" as a generic term for all instant noodles. Using a qualitative systematic literature review methodology, this study synthesizes findings from nine empirical sources to construct a comprehensive understanding of the strategic architecture behind Indomie's Nigerian success. The analysis is grounded in the OLI Paradigm (Dunning), Commercial Diplomacy Framework (Reuvers), and Brand Equity Theory (Aaker). The findings reveal that Indomie's market success in Nigeria rests on four interconnected strategic pillars: a joint venture entry strategy through Dufil Prima Foods in partnership with the Tolaram Group, product and cultural adaptation to Nigerian taste preferences and consumption contexts, sustained corporate social responsibility investments including polio vaccination programs that built community trust, and nostalgic brand positioning that transformed Indomie into a cultural institution. Empirical evidence confirms that brand elements explain approximately 60% of customer patronage variance for instant noodles in Nigeria (Ajibade Osuolale), and that nostalgic brand positioning, brand equity, and advertising are significant predictors of consumer repeat purchase behavior (Ikpeazu Ogbeide, 2026). The study concludes that Indomie's enduring competitiveness in Nigeria stems from its capacity to simultaneously function as a commercial product, a diplomatic instrument, a cultural symbol, and a community institution  a combination that no competitor has been able to replicate since Indomie first entered the Nigerian market in the late 1980s.